Kenophytes chorologically related to the habitats of railway grounds in central eastern Poland - Wrzesień, Małgorzata (Biodiversity: Research and Conservation, 2006)
The objective of the paper is to present a list of kenophytes chorologically related to the habitats of railway grounds in central eastern Poland. Out of the 950 species of vascular plants recorded there, 114 are kenophytes. Most of them often occur in different types of synanthropic habitats (Acer negundo, Amaranthus retroflexus, Cardaria draba, Chamomilla suaveolens, Conyza canadensis, Eragrostis minor, Impatiens parviflora, Medicago sativa, Sisymbrium loeselii). However, 27 demonstrate a strong connection with railway lines. They settle directly on tracks and their edges and in the vicinity of loading ramps and distribution stations. They migrate both along used railway tracks as well as those which are partially or completely excluded from use. The most pioneer habitats are taken by Amaranthus albus, Bromus japonicus, Centaurea diffusa, Erysimum marschallianum, Lepidium virginicum, Linaria repens, Oenothera subterminalis, O. wienii, Portulaca oleracea ssp. oleracea, Rubus laciniathus and Sisymbrium altissimum. On the slopes of embankments and wide edges, where the influence of the human factor is somewhat lesser, we find Artemisia dracunculus, Atriplex tatarica, Lactuca tatarica, Lathyrus nissolia, Oenothera hoelscheri, Potentilla intermedia, Sisymbrium wolgense and Vicia pannonica.